PIM-SM based Multicast Comparison for IPv4 verses IPv6 using GNS3 and JPERF - Shihab , Saif S.; Mohammed, Imad J. (Iraqi Journal of Science, 2022)
The multicast technology implements a very high-efficiency point-to-multipoint data transmission over IP networks (IPv4 and IPv6). Multicast reduces network load, eliminates traffic redundancy, and saves network bandwidth. Therefore, multicast used widely in LAN/WAN applications such as online games, video conferencing and IPTV. The multicast technology implements varied protocols such as DVMRP(Distance Vector Multicast Routing Protocol), MOSPF(Multicast Open Shortest Path First), or PIM-DM (Protocol Independent Multicast- Dense Mode) which considered source tree type, while PIM-SM (Protocol Independent Multicast- Sparse Mode) and CBT (Core Based Tree) uses shared tree. Current paper focuses on the performance evaluation of the two multicast protocols: PIM-SMv4 and PIM-SMv6 based on QoS metrics like throughput, jitter, datagram loss and Data received. PIM-SM over IPv6 showed good results compared with PIM-SM over IPv4 by 4..1%, ...1%, 65.2.% and 98.91% in terms of data received, throughput, jitter and datagram loss respectively .GNS3 simulator/emulator and JPERF used to evaluate this performance